2017
DOI: 10.1007/s00204-017-1970-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding renal nuclear protein accumulation: an in vitro approach to explain an in vivo phenomenon

Abstract: Proper subcellular trafficking is essential to prevent protein mislocalization and aggregation. Transport of the peroxisomal enzyme D-amino acid oxidase (DAAO) appears dysregulated by specific pharmaceuticals, e.g., the anti-overactive bladder drug propiverine or a norepinephrine/serotonin reuptake inhibitor (NSRI), resulting in massive cytosolic and nuclear accumulations in rat kidney. To assess the underlying molecular mechanism of the latter, we aimed to characterize the nature of peroxisomal and cyto-nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Since none of the tested, established human renal cell lines (e.g. RPTEC/TERT1) expressed endogenous DAAO, HEK293 cells were transfected with DAAO and were proven to be highly suitable to study peroxisomal trafficking and protein homeostasis as shown earlier [12]. Indeed, recent data confirmed that peroxisomes of HEK293 cells reacted in a comparable manner to rat proximal tubule epithelial cell peroxisomes in vivo (Maier et al, 2017, unpublished data).…”
Section: Co-immunoprecipitation Of Daao Interaction Partners From Hekmentioning
confidence: 82%
See 4 more Smart Citations
“…Since none of the tested, established human renal cell lines (e.g. RPTEC/TERT1) expressed endogenous DAAO, HEK293 cells were transfected with DAAO and were proven to be highly suitable to study peroxisomal trafficking and protein homeostasis as shown earlier [12]. Indeed, recent data confirmed that peroxisomes of HEK293 cells reacted in a comparable manner to rat proximal tubule epithelial cell peroxisomes in vivo (Maier et al, 2017, unpublished data).…”
Section: Co-immunoprecipitation Of Daao Interaction Partners From Hekmentioning
confidence: 82%
“…EYFP-tagged rat and human DAAO (hereafter referred to as EYFP-rDAAO and EYFP-hDAAO, respectively), and mutants lacking the PTS1 sequence (DAAO-ΔPTS) thereof were used to identify DAAO-specific interaction partners in HEK293 and WKPT cells. As described earlier [12], EYFP-rDAAO and EYFP-hDAAO were predominantly localized in peroxisomes due to the C-terminal PTS1 sequence and are subsequently referred to as DAAO perox , while the DAAO-ΔPTS mutants lacking the Cterminal PTS1 sequence were localized simultaneously in the cytosol and the nucleus [12] and are subsequently referred to as DAAO cyt . GFP-Trap ® coupled magnetic beads allowed efficient immobilization and purification of EYFP-DAAO ( Fig.…”
Section: Daao Interaction Partners In Hek293 and Wkpt Cellsmentioning
confidence: 84%
See 3 more Smart Citations